A Scoping Review of Internationalization of Dental Education—Identifying Formats and Motivations in Dental Education - Wu, Anette; Shamim, Abrar; Rahhal, Zacharie; Kieff, Monica; Lalla, Evanthia; Torre, Lynda; Zubiaurre Bitzer, Laureen; Kunzel, Carol (Frontiers in Dental Medicine, 2022)
Background Internationalization efforts, including global health activities, in dental education can play an important role in preparing future oral healthcare professionals. To date, in the available literature, there is no common understanding of what internationalization of dental education might mean, and there are no agreed upon standards relating to, or a common definition of the term internationalization of dental education. Here, the authors investigate what has been published in the above area from 01/01/2000 to 12/31/2020, identifying perceived motivations and formats. A proposed definition and connection to the field of international higher education is provided. Method A scoping review of published literature was performed and identified 47 relevant articles. The articles were thematically sorted based on educational formats and concepts (previously established in international higher education) and motivations. Results Despite the paucity of articles directly addressing internationalization of dental education, there was a large variety of articles on topics that were identified to correlate with international higher education, ranging from international partnerships, student mobility, and language, to international curriculum at home – with different perceived motivations, including competition, international understanding, and social transformation. Discussion More research on internationalization of dental education is needed to provide guidelines and formalize standards for international educational goals to better align formats and motivations for international efforts in dental education.